Assessing family resources: validation of the Swedish version of the Family Hardiness Index. Issue 4 (13th January 2016) - Persson, Carina; Benzein, Eva; Årestedt, Kristofer
Abstract : All families face normative transitions. Some are perceived as stressful and calls for family resources to maintain or restore family well‐being. In times of illness, families also need to develop strengths and capabilities to enhance family well‐being. The way these are developed is related to family hardiness. Family hardiness is thus seen as a family resource, and the Family Hardiness Index (FHI) was developed to measure family stress resistance and adaptation resources. The index was not available in Swedish and no extensive international psychometric evaluation was found. Therefore, the aim was to translate and validate the Swedish version of the FHI. The study was approved by a Regional Ethical Review Board. Data from 174 Swedish participants, family members to persons with cognitive dysfunctions (n = 95) and nursing students (n = 79) were included. Family members were enrolled in outpatient clinics in primary care and rehabilitation, and nursing students at a nursing school. Psychometric properties were evaluated through calculations of missing data, distributions of item and scale scores, item correlations, Cronbach's alpha, confirmatory factor analyses and correlations with theoretically related constructs. Sample scores had acceptable data quality, internal consistency for the FHI total scale was satisfactory (α = 0.86), and construct validity was supported. Our findings cast some doubt on the intended interpretation since confirmatory factor analyses showed that a modified four‐subscale version, excluding one subscale, showed best fit. The Control subscale lacked important psychometric properties in terms of homogeneity, internal consistency and construct validity. The sample size was probably sufficiently large for the factor analyses, but the subgroup analyses should be treated with caution. The conclusion is that the Swedish version of the FHI is a promising scale for assessing family hardiness, but more solid evidence for the factor structure in various Swedish and international samples is needed.